Whole-genome analysis showed the promotion of genetic diversity and coevolution in Staphylococcus aureus lytic bacteriophages and their hosts mediated by prophages via worldwide recombination events - Zhou, Wenyuan; Li, Yajie; Xu, Xuechao; Rao, Shengqi; Wen, Hua; Han, Yeiling; Deng, Aiping; Zhang, Zhenwen; Yang, Zhenquan; Zhu, Guoqiang (Frontiers in Microbiology, 2023)
Prophages as a part of Staphylococcus aureus genome contribute to the genetic diversity as well as survival strategies of their host. Some S. aureus prophages also have an imminent risk of host cell lysis and become a lytic phage. Nonetheless, interactions among S. aureus prophages, lytic phages, and their hosts, as well as the genetic diversity of S. aureus prophages, remain unclear. We identified 579 intact and 1389 incomplete prophages in the genomes of 493 S. aureus isolates obtained from the NCBI database. The structural diversity and gene content of intact and incomplete prophages were investigated and compared with 188 lytic phages. Mosaic structure comparison, ortholog group clustering, phylogenetic analysis, and recombination network analysis were performed to estimate genetic relatedness among S. aureus intact prophages, incomplete prophages, and lytic phages. The intact and incomplete prophages harbored 148 and 522 distinct mosaic structures, respectively. The major difference between lytic phages and prophages was the lack of functional modules and genes. Compared to the lytic phages, both the S. aureus intact and incomplete prophages harbored multiple antimicrobial resistance (AMR) and virulence factor (VF) genes. Several functional modules of lytic phages 3_AJ_2017 and 23MRA shared more than 99% nucleotide sequence identity with S. aureus intact (ST20130943_p1 and UTSW_ MRSA_55_ip3) and incomplete prophages (SA3_LAU_ip3 and MRSA_FKTN_ip4); other modules showed little nucleotide sequence similarity. Ortholog and phylogenetic analyses revealed a common gene pool shared between the prophages and lytic Siphoviridae phages. Moreover, most shared sequences existed within intact (43428/137294, 31.6%) and incomplete prophages (41248/137294, 30.0%). Therefore, the maintenance or loss of functional modules in intact and incomplete prophages is key to balance the costs and benefits of large prophages harboring various AMR and VF genes in the bacterial host. The shared identical functional modules between S. aureus lytic phages and prophages is likely to result in the exchange, acquisition, and loss of functional modules, and therefore contribute to their genetic diversity. Moreover, constant recombination events within prophages globally were responsible for the coevolution of lytic phages and their bacterial hosts.